2020
DOI: 10.18203/2394-6040.ijcmph20203371
|View full text |Cite
|
Sign up to set email alerts
|

Human and environmental risk factors of leptospirosis in Gunungkidul, Indonesia: a case-control study

Abstract: Background: Leptospirosis is a bacterial, zoonotic disease associated with environmental factors and human behavior related to occupation. This research aimed to investigate the association between human behavior and leptospirosis. Case mapping and topographical mapping were done for a comprehensive visualization.Methods: A matched case-control study design was conducted in Gunungkidul, Indonesia, from December 2017 to January 2018. Cases were selected from those reported as suspicious of leptospirosis by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…From the preliminary investigation reports and in-depth interviews, these behaviors are also risky behavior and not still resolved at this point of time. This is consistent with a previous study was reported that the habit of taking a bath or washing the clothes in the river, not using personal protection during work were associated the risk of leptospirosis [ 18 ]. Bathing in natural bodies of water was significantly associated with an increased risk of severe leptospirosis [ 19 ].…”
Section: Discussionsupporting
confidence: 93%
“…From the preliminary investigation reports and in-depth interviews, these behaviors are also risky behavior and not still resolved at this point of time. This is consistent with a previous study was reported that the habit of taking a bath or washing the clothes in the river, not using personal protection during work were associated the risk of leptospirosis [ 18 ]. Bathing in natural bodies of water was significantly associated with an increased risk of severe leptospirosis [ 19 ].…”
Section: Discussionsupporting
confidence: 93%
“…Based on the behavior of Leptospirosis sufferers in table 3, no one uses gloves when in contact with water puddles after rain (0%). Research in Gunungkidul states most of the participants had a similar habit of not using personal protection during work (19). In the research of Nursitasari (2019), it is known that there is a significant relationship between the variable contact with stagnant water on the incidence of leptospirosis in Ponorogo Regency.…”
Section: Discussionmentioning
confidence: 99%